Influence of storage on the contents of total and reducing soluble sugars in seeds of Syagrus coronata (Martius) Beccari (Arecaceae) - Rodrigues, Manuela O. Souza; Crepaldi, Iara C.; Luchese, Angélica Maria; Carvalho, Noeli O. Santana; Carvalho, Noeli O. Santana; Brito, Alone L.; Pelacani, Claudinéia R.; Ledo, Carlos A. Silva (SITIENTIBUS série Ciências Biológicas, 2005)
In the semi-arid Northeast of Brazil Syagrus coronata has great nutritional, ornamental and foraging potential. Despite its great utility this species has been subject to excecsive exploitation, which has severely reduced natural populations. The objectives of this work were to evaluate the influence of storage on total and reducing soluble sugars content in seeds of S. coronata and for the establishment of efficient conservation protocols. The experimental design was completely randomized, in a factorial scheme 4x4+1, being four storage periods, four storage conditions, and the control. The results expressed significant difference for the evaluated parameters. The contents of total and reducing soluble sugars showed oscillations among the storage periods. However, the trend was an increase of these sugars with storage time for all the storage conditions, except in the humid room. These results indicate that sugar degradation by metabolism was affected by external conditions.